The adolescent female athlete: current concepts and conundrums - Greydanus, D. E.; Omar, H.; Pratt, H. D. (Pediatric Clinics of North America, 2010)
The adolescent female athlete has become a common part of the sports environment at all levels from childhood play to professional adult sports. This article considers various issues common to this athlete to help clinicians care for their patients. Basic sports physiology is reviewed and then specific conditions are considered, including iron deficiency anemia, stress urinary incontinence, breast issues (ie, pain, asymmetry, galactorrhea, injury), the female athlete triad (ie, menstrual dysfunction, abnormal eating patterns, and osteopenia or osteoporosis), and injuries. Clinical conundrums are considered including the difficulty in caring for a dedicated athlete whose intense love of her sport may lead to menstrual and bone loss complications. The knowledgeable clinician in the twenty-first century can be of considerable help to the female athlete who is at and beyond puberty.